Mineralogical Characteristics and The Pedogenetic Processes of Soils on Coral Reefs in Ambon - Rina Devnita (Indonesian Journal on Geoscience, 2009)
http://dx.doi.org/10.17014/ijog.vol4no1.20093The mineralogical characteristics of soils developed on coral reef parent materials in Hitu and Wailiha, Ambon, were investigated regarding to the relationship to pedogenesis. The analyses concerned with the characteristics of soil chemical, physical, and mineralogy of the rock fragment and sand, silt and clay fractions are to investigate the pedogenesis processes. Both soil profiles indicate the clayey texture, slightly neutral reaction, high cation exchange capacity, base saturation, and iron oxide. The mineralogical analyses of rock fragments and sand fractions indicate that besides carbonate minerals, silicate minerals were also found. The clay mineralogy showing the domination of kaolinite, gibbsite, and goethite, reflects that the soil is intensely weathered. Pedogenesis process showing the clay translocation, indicates that the weathering process has been occuring under the tropical influence.